Personal and neighborhood low-cost monitoring to change air pollution awareness, perceptions, and behaviors: A Case Study in Gabon, Africa - Sigride Vencesla Jenniska Asseko; Robert Vancelas Obiang Zogo; Medard Obiang Ebanega; Alain Souza; Sarah E. Rothenberg; Adam Branscum; Molly L. Kile; Nordica MacCarty; Nicole S. Ngo; Perry Hystad (Journal of Environmental Studies and Sciences, 2026)

Australian native foods in gastronomy: Culture, ethics, culinary practice, and supply chains - Keely Rose Perry; Melissa A. Fitzgerald; Bronwyn Fredericks; Dale Chapman; Joseph Robert Nastasi (Food and Humanity, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

Upstate Abundance, a Variety with Small Round White Tubers and Resistance to Lineage US-23 of Late Blight and Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Barbara J. Christ; Ken M. Paddock; Matthew Falise (American Journal of Potato Research, 2026)
Upstate Abundance is a fresh market white-fleshed potato cultivar with resistance to both pathotypes Ro1 and Ro2 of the golden cyst nematode ( Globodera rostochiensis ) as well as to late blight ( Phytophthora infestans ) lineage US-23. It was selected from a cross made at Cornell University in 2000 between the Cornell breeding clone NY121 and the fresh-market cultivar Jacqueline Lee and released by the New York Agricultural Experiment Station in 2017. The tubers are small and round with modestly-recessed eyes and smooth skin; total yield across 20 trials in New York and Pennsylvania averaged 36.6 Mg ha − 1 , with about half the yield in tubers less than 4.75 cm in diameter and most of the rest in tubers between 4.75 and 6.4 cm in diameter.

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Myeloid-specific tristetraprolin mitigates postsurgical incisional pain by suppressing proinflammatory responses - Abhishek Guha; Robert E. Sorge; Ying Si; Reed Smith; Sohail M. Baig; Mohammed Amir Husain; Stacie K. Totsch; Ava M. Piper; Perry J. Blackshear; Peter H. King (Inflammation Research, 2025)
Background Proinflammatory mediators including COX-2, IL-1β, IL-6, and TNF-α, play major roles in the initiation of postsurgical pain. Produced primarily by activated macrophages and microglia, these mediators drive hyperexcitation of nociceptors and promote peripheral and central pain sensitization. Post-transcriptional RNA regulation is a major control point for these mediators, centering around adenine- and uridine-rich elements (ARE) in the 3’ untranslated regions of their mRNA transcripts. The ARE governs RNA stability and translational efficiency through an interaction with ARE-specific RNA binding proteins (AUBP). Tristetraprolin (TTP) is an AUBP that promotes RNA degradation and translational silencing of these mediators to suppress inflammatory responses. Methods Mice with myeloid-specific TTP knockout or TTP knock-in underwent paw incision and were assessed for mechanical allodynia and thermal sensitivity. Molecular and cellular inflammatory responses were monitored at the site of incision, dorsal root ganglia (DRG) and lumbar spinal cord (L-SC) by qPCR, ELISA, immunohistochemistry and/or flow cytometry. Results TTP deletion exacerbated post-incisional allodynic pain in parallel with increased edema at the site of injury and delayed wound healing but without significant effects on thermal sensitivity. There was an increase in infiltrating macrophages at the incisional site, particularly at the dermal–epidermal junction, in parallel with a robust increase in proinflammatory/pronociceptive mediators. An enhanced inflammatory response was also detected in the circulation, ipsilateral DRG and L-SC which persisted through post-incisional day 7. Conversely, TTP knock-in mice showed attenuation of allodynic pain and inflammatory responses in skin, DRG, L-SC, and circulation. Conclusion TTP plays a critical role in mitigating postsurgical pain by tamping down peripheral, central and systemic inflammatory responses, thus identifying a new target and mechanism for future development of pain therapeutics.

Development and Preliminary Evaluation of a Food Literacy Measure for Use With Young People in Canada - Tracey Borland; Michael D.T. Fung; Emily Taylor; Michael Chaiton; Robert Schwartz; Heather Thomas; Elsie Azevedo Perry; H. Ruby Samra; Lucy Valleau; Sharon I. Kirkpatrick (Journal of the Academy of Nutrition and Dietetics, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Advances in our understanding of the estrous cycle and applications for improving targeted reproductive management in livestock - Robert A. Cushman; Shelby L. Rosasco; Kacie L. McCarthy; Alexandria P. Snider; George A. Perry; Clay A. Lents (Domestic Animal Endocrinology, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

A Community-Based Health Risk Assessment Following the Gold King Mine Spill: Results from the Gold King Mine Spill Diné Exposure Project - Yoshira Ornelas Van Horne; Karletta Chief; Perry H. Charley; Mae-Gilene Begay; Nathan Lothrop; Robert A. Canales; Paloma I. Beamer (Exposure and Health, 2024)

Developmental programming of the ovarian reserve in livestock - Robert A. Cushman; Vahid Akbarinejad; George A. Perry; Clay A. Lents (Animal Reproduction Science, 2024)

Brodie, a Dual-Purpose Chipping and Tablestock Variety with Resistance to Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode and Partial Resistance to Pathotype Pa2/3 of the Pale Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Louise-Marie Dandurand; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2024)

Sea level rise adaptation pushes an insular endemic rodent closer to extinction - Paul J. Taillie; Sandra Sneckenberger; Neil Perry; Chad Anderson; Kevin Kalasz; Robert A. McCleery (Biodiversity and Conservation, 2023)
Understanding how species will respond to a rapidly changing global climate is requisite to conserving biodiversity. Though habitat losses from human development and land use change remain the most critical threats to biodiversity globally, some regions, such as low-lying islands, are particularly vulnerable to the effects of climate change. Despite this vulnerability, there may be opportunities for imperiled species on islands to adapt to the effects of climate-induced sea level rise. To understand how the response to rising seas may influence the amount of future habitat, we investigated shifts in the elevational range of the endangered silver rice rat ( Oryzomys palustris natator; hereafter “rice rat”), a species endemic to tidal environments of the Lower Florida Keys, USA. We quantified fine-scale habitat use using radio telemetry of collared animals, first in 2004, and again in 2021, thus spanning a 17-year period during which the local sea level rose by 0.142 m. We observed a shift in the elevational range limits of rice rats which closely mirrored the rise in sea level, and that this apparent ability to adapt to rising sea level decreased the extent of habitat loss in subsequent decades. However, over longer time scales (~ 100 yrs), the extent of habitat loss from sea level rise outpaced rice rats’ ability to adapt. As such, the conservation of biodiversity on low-lying islands hinges on the ability of the global community to decrease anthropogenic greenhouse gas emissions and mitigate the associated consequences for the global climate. Otherwise, conservation practitioners will be increasingly forced to make difficult decisions about how to conserve imperiled species on low-lying islands.

Examining the performance of alternative harvest regulations for short-lived taxa: A case study of Florida Bay scallop management - Lisa Chong; Nicholas Fisch; John Scott Borsum; Jennifer Granneman; Diana Perry; Gabrielle Love; Brittany Hall-Scharf; Robert Botta; Kai Lorenzen; Edward Camp; Zachary Siders (Fisheries Research, 2023)

Geography, environment, and colonization history interact with morph type to shape genomic variation in an Arctic fish - Sarah J. Salisbury; Robert Perry; Don Keefe; Gregory R. McCracken; Kara K. S. Layton; Tony Kess; Ian R. Bradbury; Daniel E. Ruzzante (Molecular Ecology, 2023)
Polymorphic species are useful models for investigating the evolutionary processes driving diversification. Such processes include colonization history as well as contemporary selection, gene flow, and genetic drift, which can vary between intraspecific morphs as a function of their distinct life histories. The interactive and relative influence of such evolutionary processes on morph differentiation critically informs morph‐specific management decisions and our understanding of incipient speciation. We therefore investigated how geographic distance, environmental conditions, and colonization history interacted with morph migratory capacity in the highly polymorphic fish species, Arctic Charr ( Salvelinus alpinus ). Using an 87 k SNP chip we genetically characterized recently evolved anadromous, resident, and landlocked charr collected from 45 locations across a secondary contact zone of three charr glacial lineages in eastern Canada. A strong pattern of isolation by distance across all populations suggested geographic distance principally shaped genetic structure. Landlocked populations had lower genetic diversities and higher genetic differentiation than anadromous populations. However, effective population size was generally temporally stable in landlocked populations in comparison to anadromous populations. Genetic diversity positively correlated with latitude, potentially indicating southern anadromous populations' vulnerability to climate change and greater introgression between the Arctic and Atlantic glacial lineages in northern Labrador. Local adaptation was suggested by the observation of several environmental variables strongly associating with functionally relevant outlier genes including a region on chromosome AC21 potentially associated with anadromy. Our results demonstrate that gene flow, colonization history, and local adaptation uniquely interact to influence the genetic variation and evolutionary trajectory of populations.

Lehigh, a Variety with Yellow Flesh and Resistance to the Golden Cyst Nematode and Common Scab - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Factors affecting year‐class strength and growth of lake whitefish ( Coregonus clupeaformis ) in impounded lakes as revealed by otolith chronologies - Robert C. Perry; John M. Casselman (Journal of Fish Biology, 2022)
Recruitment and growth rates for lake whitefish ( Coregonus clupeaformis ) inhabiting the Smallwood Reservoir, Labrador, Canada, were influenced by facets of its creation and the temporal variability in water levels associated with its operation. Filling of the reservoir between 1971 and 1974 created a concurrent increase in lake whitefish recruitment above long‐term averages. In addition, recruitment was influenced by winter drawdown levels: higher water levels during February enhanced recruitment, accounting for an additional 10% of the long‐term variation in recruitment. Using otolith increments as a growth index, the authors determined that growth was influenced by reservoir creation. Growth rates during the initial period of flooding (1971–1975) exceeded long‐term averages and were greater than those in any other 5‐year period between 1965 and 1995. Growth rate increases were attributed to a simultaneous zooplankton bloom. After exceptional growth, lake whitefish showed a period (1976–1980) when growth rates decreased. The authors developed a quantitative technique using otoliths as an index to establish chronologies of fish growth rates. The index can be used to quantify and assess the impacts of reservoir hydrology on fish populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Sex-based changes in rat brain serotonin and behavior in a model of altitude-related vulnerability to treatment-resistant depression - Shami Kanekar; Chandni Sheth; Hendrick Ombach; Jadeda Brown; Michael Hoffman; Robert Ettaro; Perry Renshaw (Psychopharmacology, 2021)

Park Visitors’ Place Attachment and Climate Change-related Displacement: Potential Shifts in Who, Where, and When - Elizabeth E. Perry; Xiao Xiao; John M. Nettles; Tatiana A. Iretskaia; Robert E. Manning (Environmental Management, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Harbor Seals as Sentinels of Ice Dynamics in Tidewater Glacier Fjords - Jamie N. Womble; Perry J. Williams; Robert W. McNabb; Anupma Prakash; Rudiger Gens; Benjamin S. Sedinger; Cheyenne R. Acevedo (Frontiers in Marine Science, 2021)
Tidewater glaciers calve icebergs into the marine environment which serve as pupping, molting, and resting habitat for some of the largest seasonal aggregations of harbor seals ( Phoca vitulina richardii ) in the world. Although they are naturally dynamic, advancing and retreating in response to local climatic and fjord conditions, most tidewater glaciers around the world are thinning and retreating. Climate change models predict continued loss of land-based ice with unknown impacts to organisms such as harbor seals that rely on glacier ice as habitat for critical life history events. To understand the impacts of changing ice availability on harbor seals, we quantified seasonal and annual changes in ice habitat in Johns Hopkins Inlet, a tidewater glacier fjord in Glacier Bay National Park in southeastern Alaska. We conducted systematic aerial photographic surveys ( n = 55) of seals and ice during the pupping (June; n = 30) and molting (August; n = 25) periods from 2007 to 2014. Object-based image analysis was used to quantify the availability and spatial distribution of floating ice in the fjord. Multivariate spatial models were developed for jointly modeling stage-structured seal location data and ice habitat. Across all years, there was consistently more ice in the fjord during the pupping season in June than during the molting season in August, which was likely driven by seasonal variation in physical processes that influence the calving dynamics of tidewater glaciers. Non-pup harbor seals and ice were correlated during the pupping season, but this correlation was reduced during the molting season suggesting that harbor seals may respond to changes in habitat differently depending upon trade-offs associated with life history events, such as pupping and molting, and energetic costs and constraints associated with the events.

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Waneta, a Variety with Excellent Chip Color out of Cold Storage, Long Tuber Dormancy, and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

Steps to Develop Early Warning Systems and Future Scenarios of Storm Wave-Driven Flooding Along Coral Reef-Lined Coasts - Gundula Winter; Curt Storlazzi; Sean Vitousek; Ap van Dongeren; Robert McCall; Ron Hoeke; William Skirving; John Marra; Johan Reyns; Jerome Aucan; Matthew Widlansky; Janet Becker; et al. (Frontiers in Marine Science, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Reef Habitat Type and Spatial Extent as Interacting Controls on Platform-Scale Carbonate Budgets - Chris T. Perry; Kyle M. Morgan; Robert T. Yarlett (Frontiers in Marine Science, 2017)

Lamoka, a Variety with Excellent Chip Color Out of Cold Storage and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2017)

Twenty years of ModelDB and beyond: building essential modeling tools for the future of neuroscience - Robert A. McDougal; Thomas M. Morse; Ted Carnevale; Luis Marenco; Rixin Wang; Michele Migliore; Perry L. Miller; Gordon M. Shepherd; Michael L. Hines (Journal of Computational Neuroscience, 2017)

Salbutamol effects on systemic potassium dynamics during and following intense continuous and intermittent exercise - Muath M. Altarawneh; Aaron Petersen; Robert Smith; David M. Rouffet; Francois Billaut; Ben D. Perry; Victoria L. Wyckelsma; Antony Tobin; Michael J. McKenna (European Journal of Applied Physiology, 2016)

A portrait of a sucker using landscape genetics: how colonization and life history undermine the idealized dendritic metapopulation - Sarah J. Salisbury; Gregory R. McCracken; Donald Keefe; Robert Perry; Daniel E. Ruzzante (Molecular Ecology, 2016)
Dendritic metapopulations have been attributed unique properties by in silico studies, including an elevated genetic diversity relative to a panmictic population of equal total size. These predictions have not been rigorously tested in nature, nor has there been full consideration of the interacting effects among contemporary landscape features, colonization history and life history traits of the target species. We tested for the effects of dendritic structure as well as the relative importance of life history, environmental barriers and historical colonization on the neutral genetic structure of a longnose sucker ( Catostomus catostomus ) metapopulation in the Kogaluk watershed of northern Labrador, Canada. Samples were collected from eight lakes, genotyped with 17 microsatellites, and aged using opercula. Lakes varied in differentiation, historical and contemporary connectivity, and life history traits. Isolation by distance was detected only by removing two highly genetically differentiated lakes, suggesting a lack of migration–drift equilibrium and the lingering influence of historical factors on genetic structure. Bayesian analyses supported colonization via the Kogaluk's headwaters. The historical concentration of genetic diversity in headwaters inferred by this result was supported by high historical and contemporary effective sizes of the headwater lake, T‐Bone. Alternatively, reduced allelic richness in headwaters confirmed the dendritic structure's influence on gene flow, but this did not translate to an elevated metapopulation effective size. A lack of equilibrium and upstream migration may have dampened the effects of dendritic structure. We suggest that interacting historical and contemporary factors prevent the achievement of the idealized traits of a dendritic metapopulation in nature.

A genetic discontinuity in moose (Alces alces) in Alaska corresponds with fenced transportation infrastructure - Robert E. Wilson; Sean D. Farley; Thomas J. McDonough; Sandra L. Talbot; Perry S. Barboza (Conservation Genetics, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Regional‐scale dominance of non‐framework building corals on Caribbean reefs affects carbonate production and future reef growth - Chris T. Perry; Robert S. Steneck; Gary N. Murphy; Paul S. Kench; Evan N. Edinger; Scott G. Smithers; Peter J. Mumby (Global Change Biology, 2015)
Coral cover on Caribbean reefs has declined rapidly since the early 1980's. Diseases have been a major driver, decimating communities of framework building Acropora and Orbicella coral species, and reportedly leading to the emergence of novel coral assemblages often dominated by domed and plating species of the genera Agaricia , Porites and Siderastrea . These corals were not historically important Caribbean framework builders, and typically have much smaller stature and lower calcification rates, fuelling concerns over reef carbonate production and growth potential. Using data from 75 reefs from across the Caribbean we quantify: (i) the magnitude of non‐framework building coral dominance throughout the region and (ii) the contribution of these corals to contemporary carbonate production. Our data show that live coral cover averages 18.2% across our sites and coral carbonate production 4.1 kg Ca CO 3 m −2 yr −1 . However, non‐framework building coral species dominate and are major carbonate producers at a high proportion of sites; they are more abundant than Acropora and Orbicella at 73% of sites; contribute an average 68% of the carbonate produced; and produce more than half the carbonate at 79% of sites. Coral cover and carbonate production rate are strongly correlated but, as relative abundance of non‐framework building corals increases, average carbonate production rates decline. Consequently, the use of coral cover as a predictor of carbonate budget status, without species level production rate data, needs to be treated with caution. Our findings provide compelling evidence for the Caribbean‐wide dominance of non‐framework building coral taxa, and that these species are now major regional carbonate producers. However, because these species typically have lower calcification rates, continued transitions to states dominated by non‐framework building coral species will further reduce carbonate production rates below ‘predecline’ levels, resulting in shifts towards negative carbonate budget states and reducing reef growth potential.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Persistent neurocognitive decline in a clinic sample of hepatitis C virus-infected persons receiving interferon and ribavirin treatment - Jordan E. Cattie; Scott L. Letendre; Steven Paul Woods; Fatma Barakat; William Perry; Mariana Cherner; Anya Umlauf; Donald Franklin; Robert K. Heaton; Tarek Hassanein; Igor Grant (Journal of NeuroVirology, 2014)

Development of 26 novel microsatellite makers for the round whitefish (Prosopium cylindraceum) and successful polymorphic cross-specific amplification of seven previously developed salmonid markers - Gregory R. McCracken; Kristen L. Wilson; Hilary T. Brewis; Meghan C. McBride; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development and characterization of 36 novel microsatellite markers for lake chub (Couesius plumbeus) using illumina paired-end sequencing - Gregory R. McCracken; Hilary T. Brewis; Meghan C. McBride; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Novel mitochondrial DNA primers for identification of population trends in longnose suckers (Catostomus catostomus) and multispecies identification - Barbara L. Langille; Robert Perry; Donald Keefe; H. Dawn Marshall (Conservation Genetics Resources, 2014)

Development of 17 novel microsatellite markers for the longnose sucker (Catostomus catostomus) and successful cross-specific amplification of 14 previously developed markers from congeneric species - Gregory R. McCracken; Kristen L. Wilson; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Establishing a reference group for distal 18q-: clinical description and molecular basis - Jannine D. Cody; Minire Hasi; Bridgette Soileau; Patricia Heard; Erika Carter; Courtney Sebold; Louise O’Donnell; Brian Perry; Robert F. Stratton; Daniel E. Hale (Human Genetics, 2014)

The Influence of Freshwater on Nekton Community Structure in Hydrologically Distinct Basins in Northeastern Florida Bay, FL, USA - Kerry E. Flaherty; Richard E. Matheson; Robert H. McMichael; William B. Perry (Estuaries and Coasts, 2013)

Effects of a novel mGlu2/3 receptor agonist prodrug, LY2140023 monohydrate, on central monoamine turnover as determined in human and rat cerebrospinal fluid - Stephen Lowe; Robert Dean; Bradley Ackermann; Kimberley Jackson; Fanni Natanegara; Shelby Anderson; James Eckstein; Eunice Yuen; Mosun Ayan-Oshodi; Mary Ho; David McKinzie; Kenneth Perry; et al. (Psychopharmacology, 2012)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

FUS Immunogold Labeling TEM Analysis of the Neuronal Cytoplasmic Inclusions of Neuronal Intermediate Filament Inclusion Disease: A Frontotemporal Lobar Degeneration with FUS Proteinopathy - Tristan Page; Michael A. Gitcho; Sabrina Mosaheb; Deborah Carter; Sumi Chakraverty; Robert H. Perry; Eileen H. Bigio; Marla Gearing; Isidre Ferrer; Alison M. Goate; Nigel J. Cairns; Julian R. Thorpe (Journal of Molecular Neuroscience, 2011)

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Effectiveness of medical equipment donations to improve health systems: how much medical equipment is broken in the developing world? - Lora Perry; Robert Malkin (Medical & Biological Engineering & Computing, 2011)

Polyamines are required for the expression of key Hms proteins important for Yersinia pestis biofilm formation - Brian W. Wortham; Marcos A. Oliveira; Jacqueline D. Fetherston; Robert D. Perry (Environmental Microbiology, 2010)
Summary We previously showed that mutations in the genes encoding the two main biosynthetic enzymes responsible for polyamine production, arginine decarboxylase (SpeA) and ornithine decarboxylase (SpeC) cause a loss of biofilm formation in Yersinia pestis . In Y. pestis the development of a biofilm is dependent on 6 Hms (hemin storage) proteins (HmsH, F, R, S, T and P) grouped into 3 operons; hmsHFRS , hmsT and hmsP . In this article we show that polyamines are necessary to maintain the levels of key Hms proteins. In the absence of polyamines there is an ∼93%, ∼43% and ∼90% reduction in protein levels of HmsR, HmsS and HmsT respectively. Overexpression of hmsR and hmsT from plasmids alone can restore biofilm formation to a SpeA ‐ SpeC ‐ mutant. Addition of exogenous putrescine also restores normal levels of HmsR, HmsS, HmsT and biofilm production. Analyses using transcriptional reporters and quantitative RT‐PCR indicate that the initiation of transcription and mRNA stability are not reduced by polyamine deficiency. Instead, translational reporters indicate that polyamines function at least in part by modulating the translation of HmsR and HmsT. Although construction of a consensus Shine–Dalgarno sequence upstream of hmsT modestly reduced the stimulation of translation by putrescine, additional mechanisms likely contribute to the polyamine‐dependent expression of HmsT. Finally, we have shown that polyamines play a role in bubonic plague.

Primary Productivity in 20-year Old Created Wetlands in Southwestern Virginia - Robert B. Atkinson; James E. Perry; Gregory B. Noe; W. Lee Daniels; John Cairns (Wetlands, 2010)

Yersinia ironomics: comparison of iron transporters among Yersinia pestis biotypes and its nearest neighbor, Yersinia pseudotuberculosis - Stanislav Forman; James T. Paulley; Jacqueline D. Fetherston; Yi-Qiang Cheng; Robert D. Perry (BioMetals, 2010)

The effects of bottom-up target luminance and top-down spatial target predictability on saccadic reaction times - Robert A. Marino; Douglas Perry Munoz (Experimental Brain Research, 2009)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Insights into Yersinia pestis biofilm development: topology and co‐interaction of Hms inner membrane proteins involved in exopolysaccharide production - Alexander G. Bobrov; Olga Kirillina; Stanislav Forman; Dietrich Mack; Robert D. Perry (Environmental Microbiology, 2008)
Summary Primarily, three operons, hmsHFRS, hmsT and hmsP , are responsible for the development of a Yersinia pestis biofilm, which is essential for blockage‐dependent transmission of plague from fleas to mammals. Here, using specific antibodies, a polymeric β‐1,6‐ N ‐acetyl‐ d ‐glucosamine‐like polysaccharide was detected in the extracellular matrix of hmsHFRS ‐dependent Y. pestis biofilm. The production of this exopolysaccharide (EPS) was controlled by diguanylate cyclase HmsT and EAL domain phosphodiesterase HmsP, acting as positive and negative regulators respectively. Cellular compartmentalization of soluble segments of Hms inner membrane proteins, including the putative glycosyltransferase domain of HmsR, the diguanylate cyclase/GGDEF domain of HmsT and the phosphodiesterase/EAL domain of HmsP, was determined by a combination of topology prediction algorithms and construction of C‐terminal translational fusions with β‐galactosidase and alkaline phosphatase. Multiple interactions of Hms inner membrane proteins were detected using bacterial cAMP based two‐hybrid system. Biochemical analyses confirmed some of these protein–protein interactions. Our results indicate that synthesis and regulation of the Y. pestis biofilm EPS occurs in the cytoplasm by a proposed Hms enzymatic complex.

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

An intronic sequence mutated in flexed-tail mice regulates splicing of Smad5 - Shailaja Hegde; Laurie E. Lenox; Andrew Lariviere; Prashanth Porayette; John M. Perry; Michele Yon; Robert F. Paulson (Mammalian Genome, 2007)

Roles of the Yfe and Feo transporters of Yersinia pestis in iron uptake and intracellular growth - Robert D. Perry; Ildefonso Mier; Jacqueline D. Fetherston (BioMetals, 2007)

Groundwater abstraction impacts on spring flow and base flow in the Hillsborough River Basin, Florida, USA - Kenneth A. Weber; Robert G. Perry (Hydrogeology Journal, 2006)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Neural correlates of conflict processing - Robert West; Kristin Jakubek; Nicholas Wymbs; Michele Perry; Kara Moore (Experimental Brain Research, 2005)

Vegetation Communities of 20-year-old Created Depressional Wetlands - Robert B. Atkinson; James E. Perry; John Cairns (Wetlands Ecology and Management, 2005)

Hydrogeology Journal in 2004 - Clifford Voss; Perry Olcott; Robert Schneider; Christine Watson (Hydrogeology Journal, 2004)

Phosphonates and particulate organic phosphorus cycling in an anoxic marine basin - C. R. Benitez-Nelson; Lauren O'Neill; Lauren C. Kolowith; Perry Pellechia; Robert Thunell (Limnology and Oceanography, 2004)
Total particulate phosphorus (TPP), particulate inorganic P (PIP), and particulate organic P (POP) concentrations were measured in a year‐long series of sediment trap samples collected throughout the oxic‐anoxic water column (275 m, 455 m, 930 m, and 1,255 m) of the Cariaco Basin. TPP, PIP, and POP fluxes varied seasonally and decreased significantly with depth, from 65 to 19 µmol TPP m −2 d −1 , 43 to 8 µmol PIP m −2 d −1 , and 22 to 11 µmol POP m −2 d −1 . Significant flux relationships (p 31 P nuclear magnetic resonance (NMR), and it was found that phosphonates, chemically and thermally inert compounds, are a significant fraction of the TPP pool. Furthermore, these compounds were preferentially removed relative to more bioavailable P esters during a low flux event. Their selective removal suggests that these compounds may be an unrecognized source of bioavailable P under anoxic conditions.

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Editors? Message - Clifford Voss; Perry Olcott; Robert Schneider (Hydrogeology Journal, 2004)

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

Hydrogeology Journal in 2002 - Perry Olcott; Robert Schneider; Clifford Voss (Hydrogeology Journal, 2003)

PINNIPED SURVIVAL IN CAPTIVITY: ANNUAL SURVIVAL RATES OF SIX SPECIES - Simona Perry Roberts; Douglas P. Demaster (Marine Mammal Science, 2001)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

DNA fingerprinting evidence of nonfilial nursing in grey seals - ELIZABETH A. PERRY; DARYL J. BONESS; ROBERT C. FLEISCHER (Molecular Ecology, 1998)
We tested the hypothesis that kin selection may play a role in fostering behaviour in grey seals. Fostering frequency varied among three colonies, ranging from 3% to 28%. Band‐sharing coefficients (S) of DNA fingerprints, from two multilocus probes, were used to predict relatedness ( r ). Mean r did not differ between foster mother‐pup pairs and the expected r = 0 for presumed unrelated female‐pup pairs. Likewise, mean r between fostered and filial pups compared to r between presumed unrelated pups within the same beaches did not differ. Mean S values of presumed unrelated pups on different beaches within the two smallest colonies were indistinguishable, indicating that there is not increased variation in relatedness in small colonies. These results suggest that kin selection does not play a significant role in the maintenance of grey seal fostering behaviour.

In vivo and in vitro swelling of cell walls during fruit ripening - Robert J. Redgwell; Elspeth MacRae; Ian Hallett; Monica Fischer; Jo Perry; Roger Harker (Planta, 1997)

A potato breeding technique used for Texas - Bruce A. Perry; Robert V. Akeley; W. B. Cook (American Journal of Potato Research, 1960)